Experimental HTLV-I and associated myelopathy - CARLOS M. DE CASTRO COSTA; EBERVAL G. DE FIGUEIREDO; TEREZINHA J.T. SANTOS; CARINA H. FROTA; CARMEN C.G. LOBO; FRANKLIN J.C. SANTOS; RAIMUNDO N. ALCÂNTARA; RODRIGO S.N. RAMOS; TARCÍSIO T.S. ROCHA; TRÍCIA F. NOGUEIRA (Arquivos de Neuro-Psiquiatria)
HTLV-I infection and associated myelopathy has been reproduced experimentally in vitro and in vivo and these studies have shown the possibility of creating several lines of infective cells and of detecting minor and major clinical expressions of HTLV-I associated myelopathy in rabbits and rats.